1990
DOI: 10.1073/pnas.87.12.4814
|View full text |Cite
|
Sign up to set email alerts
|

Structural correlates of high antibody affinity: three engineered amino acid substitutions can increase the affinity of an anti-p-azophenylarsonate antibody 200-fold.

Abstract: Communicated by Alfred Nisonoff, April 9, 1990 (received for review February 22, 1990 ABSTRACTThe basis for the 200-fold difference in affinity between two hybridoma antibodies specific for the hapten p-azophenylarsonate (Ars) that have diversified by somatic hypermutation was examined. Oligonucleotide-directed mutagenesis was used to sequentially convert the nucleotide sequence ofthe lower-affinity antibody into that ofthe higher-affinity one, and the mutant antibodies generated by transfection of hybridoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 34 publications
5
53
0
Order By: Relevance
“…A significant, perhaps unexpected, consequence of receptor plasticity was that it also allowed for a convergence of Ab reactivities, with binding affinities being well within the range described for primary immune responses (12,(42)(43)(44). Notably, this was predominantly supported by entropy-controlled binding pathways and required varying degrees of adaptability by the individual germline Abs.…”
Section: Paratope Plasticity and Degeneracy Of Ag Recognitionmentioning
confidence: 99%
“…A significant, perhaps unexpected, consequence of receptor plasticity was that it also allowed for a convergence of Ab reactivities, with binding affinities being well within the range described for primary immune responses (12,(42)(43)(44). Notably, this was predominantly supported by entropy-controlled binding pathways and required varying degrees of adaptability by the individual germline Abs.…”
Section: Paratope Plasticity and Degeneracy Of Ag Recognitionmentioning
confidence: 99%
“…It was also shown that, taken together, the 11 L chain mutations in 36 -71 Ab do not affect Ab affinity, as expression of 36 -71 H chain with either 36 -71L or 36 -65L resulted in Abs with indistinguishable affinity, despite the fact that several L chain mutations in 36 -71 are in CDRs ( Fig. 1) (11). Thus, high-affinity binding in 36 -71 was associated with mutations in the H chain.…”
mentioning
confidence: 93%
“…The production of the murine A/J hybridoma cell lines 36 -65 and 36 -71 (␥1, ), and 36 -65 and 36 -71 transfectomas (IgG2b (␥ 2 b), ) and their H chain loss variants 36 -65L and 36 -71L were previously described (4,11,15). …”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations